Effects of Polymorphisms in the Serotonin Transporter Promoter-Linked Polymorphic Region on Postthoracotomy Pain Severity - Kimura, Aya (J Pain Res, 2021)
PURPOSE: Serotonin (5-HT) is highly associated with pain modulation. The human 5-HT transporter (5-HTT) gene (SLC6A4) features several polymorphisms in its promoter region (5-HTTLPR) that affect the 5-HTT expression. The S allele of 5-HTTLPR induces low 5-HT tone, and it may influence the modulation of chronic pain. Meanwhile, pain occurs in 40–50% of patients after thoracic surgery, and its mechanism remains under investigation. This study assessed the role of 5-HTTLPR polymorphisms in postthoracotomy pain severity. PATIENTS AND METHODS: A total of 178 patients undergoing pneumonectomy were enrolled. The genotypes of 5-HTTLPR were divided into two groups: S/S group and S/L or L/L group. Linear mixed-effects models were used to assess the association between 5-HTTLPR genotypes and the numerical rating scale (NRS) score change over time. RESULTS: Among the participants, data were obtained for 162 patients. The genotype distribution was as follows: S/S, 67.3%; S/L or L/L, 32.7%. No significant difference in patient characteristics was found between the genotype groups. There was no significant interaction between the 5-HTTLPR genotypes and the NRS score change over time (p = 0.842). CONCLUSION: Polymorphisms in 5-HTTLPR were not associated with postthoracotomy pain severity.